2019
DOI: 10.3389/fped.2019.00002
|View full text |Cite
|
Sign up to set email alerts
|

Emphysematous Pyelonephritis Following Ureterovesical Reimplantation for Congenital Obstructive Megaureter. Pediatric Case Report and Review of the Literature

Abstract: Introduction: Emphysematous pyelonephritis (EPN) is a rare, life-threatening necrotizing infection of the kidney. To date, very few cases of EPN have been described in the pediatric age. The first case of EPN in a toddler occurring after ureterovesical reimplantation for congenital obstructive megaureter is reported with a literature review.Case Report: A 23-month-old male, with a prenatal diagnosis of obstructive megaureter and incomplete duplication of the left urinary tract, was admitted to our Unit where h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
(54 reference statements)
0
13
0
3
Order By: Relevance
“…It was found that in all age periods studied by us, the average diameter of the renal vein in males prevailed over that in females, but without a significant difference (Kafarov et al, 2019;Kostilenko and Azmi, 2008;Girgenti et al, 2019).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…It was found that in all age periods studied by us, the average diameter of the renal vein in males prevailed over that in females, but without a significant difference (Kafarov et al, 2019;Kostilenko and Azmi, 2008;Girgenti et al, 2019).…”
Section: Resultsmentioning
confidence: 80%
“…Currently, in the scientific literature, there is no unequivocal opinion regarding issues related to the diameters of the renal veins, the knowledge of which is of great clinical importance (Tarabarko, 1995;Shumakov, 2005;Monina, 2014;Russell et al, 2019;Barabanov, 2001;Fulop et al, 2020;Mochalov, 2006;Kafarov et al, 2017;Xu et al, 2021;Jannatbabaei et al, 2019;Jiang et al, 2019;Kafarov et al, 2015;Kvyatkovskaya et al, 2000;Wang et al, 2008;Kafarov et al, 2019;Kostilenko and Azmi, 2008;Girgenti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Het voorkomen van EPN bij kinderen is echter zeer zeldzaam en is voor het eerst door Pode et al beschreven in 1985 bij een 10-jarige vrouwelijke patiënt [3]. Tot op heden zijn er van EPN bij kinderen acht casus verschenen [3][4][5][6][7][8][9].…”
Section: Discussieunclassified
“…Bij kinderen wordt diabetes niet als risicofactor beschreven. De eerder gepubliceerde casus laten zien dat nefro-urolithiase, gestoorde immuniteit en obstructieve uropathie de voornaamste risicofactoren lijken te zijn [3][4][5][6][7][8][9]. In de hier beschreven casus lijkt een PUJ-stenose op basis van overkruisende vaten de oorzakelijke factor.…”
Section: Discussieunclassified
See 1 more Smart Citation